New species of Neanuridae (Collembola) living on the endemic tree Zelkova abelicea in Crete - Smolis, Adrian; Skarżyński, Dariusz; Gwiazdowicz, Dariusz J. (Zootaxa, 2023)
Six new species from Crete belonging to the family Neanuridae are described and illustrated in detail. Friesea schulzi sp. nov. is characterized by having white body, 3 + 3 ocelli, 4 anal spines and furca and retinaculum absent (stage 5). Friesea cretensis sp. nov. can be easily identified by 5 + 5 ocelli, 4 anal spines and 6 microchaetae in furcal field. Characteristic and recognizable character of Pseudachorutella ellisi sp. nov. is very long buccal cone. Deutonura schulzi sp. nov. differs from other taxa in the genus in the presence of internal tooth on claw. Endonura zelkovae sp. nov. is especially distinctive due to the presence 3+s and 4+s chaetae De on Th. II and III. The main characteristics of Cryptonura ellisi sp. nov. include a massive mandibles and high number of mandibular teeth.